MEDIA PEMBELAJARAN LINGKARAN BERBASIS GEOGEBRA APPLET UNTUK PENGUATAN KEMAMPUAN BERPIKIR KREATIF - Fitria Sulistyowati; Arif Usman; Esti Harini (Delta: Jurnal Ilmiah Pendidikan Matematika, 2022)
This research is development research that was held on in August 2021 and aims to produce a circle learning media based on Geogebra Applets to reinforce the creative thinking ability of students in class XI of Senior High School. The development method used in this research is the first three steps in the 4-D development model consisting of: (1) define; (2) designs; (3) develop and limited to validity and practicality tests. Data at the define stage was collected using the documentation method, while at the development stage it was collected using a content validity questionnaire and student response questionnaires which were then analyzed descriptively by statistical analysis. This study gives the results that: (1) the circle learning media based on Geogebra Applet that was developed, is very valid with an average score of 3.83; (2) students gave a very good response with a percentage of 86.48% of the circle learning media. These results indicate that the circle learning media based on the Geogebra Applet that was developed is valid and practical. This research is expected to be a reference for further research related to the development of learning media based on Geogebra Applet.